ELTV Week-in-Review (African Knowledges and the History Publication since the 1970s, 1985)
News on various topics, including Liberia's economic situation and investors' confidence, as well as a speech by the President of Liberia, Samuel Kanyon Doe, expressing support.
Keywords: News; Public Affairs